Constraints to the development, operation and maintenance of spate irrigation schemes in Ethiopia - Erkossa, Teklu; Langan, Simon J.; Hagos, Fitsum (2014)
Flood-based farming is among the potential options in ensuring access to water for crop and livestock production for small-scale farmers in the arid and semiarid lowlands of sub-Saharan Africa, and Ethiopia in particular. Flood-based irrigation while inexpensive is rooted in tradition in many rural communities which is in contrast to many other irrigation types which are unavailable (in terms of water source, technology or capacity) or are costly to develop. Spate irrigation has been practiced in different parts of Ethiopia for many decades, but it was only recently that it gained the government’s attention. This study was conducted through a review and informal discussion with the objectives of documenting the current status, trends and prospects of spate irrigation in the country and the associated challenges, taking cases of selected schemes in different regional states. The study revealed that spate irrigation is expanding either through improvement of traditional schemes or by developing new ones. Neither the traditional nor modern schemes are free of challenges. The traditional schemes suffer from floods that damage their diversion structures, while poor design and construction of diversion structures have led to the failure of new ones. A range of socio-technical improvements in the planning, implementation and operation of schemes is proposed, including the design of headworks and canals consistent with the size and nature of expected flows, structures to minimize sedimentation, building capacity of farmers and district officers, and monitoring and improving the management that currently adversely impacts the performance of the schemes. Consulting farmers at every stage of the development, and building the capacity of engineers to deal with the unique nature of spate flows are the most likely interventions to ensure successful agricultural production using spate irrigation.